2017
DOI: 10.5603/cj.a2017.0032
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic evaluation of diastolic functions in patients with polycystic ovary syndrome: A comperative study of diastolic functions in sub-phenotypes of polycystic ovary syndrome

Abstract: Background: Polycystic ovary syndrome (PCOS) is a heterogeneous endocrine disorder among reproductive-aged women. It is known to be associated with cardiovascular diseases. The aim of this (Cariol J 2017; 24, 4: 364-373)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…found that hyperandrogenism, value of free androgen index (FAI) > 4.5, waist circumference and waist-to-hip ratio (WHR) were independently associated with higher risk of MetS in logistic regression analysis. 29 Several East Asian, [30][31][32] South Asian, 33,34 Middle Eastern, 35 Turkish 36 and Latin American 37,38 studies demonstrated comparable prevalence of MetS between the four PCOS phenotypes, regardless of BMI of the groups, while others showed highest prevalence of MetS in NIH phenotypes, 12,14,22,39,40 especially in phenotype I. [41][42][43] Similar to Caucasian studies, MetS or its individual components were more frequently diagnosed in PCOS than in controls.…”
Section: Metabolic Syndromementioning
confidence: 73%
See 2 more Smart Citations
“…found that hyperandrogenism, value of free androgen index (FAI) > 4.5, waist circumference and waist-to-hip ratio (WHR) were independently associated with higher risk of MetS in logistic regression analysis. 29 Several East Asian, [30][31][32] South Asian, 33,34 Middle Eastern, 35 Turkish 36 and Latin American 37,38 studies demonstrated comparable prevalence of MetS between the four PCOS phenotypes, regardless of BMI of the groups, while others showed highest prevalence of MetS in NIH phenotypes, 12,14,22,39,40 especially in phenotype I. [41][42][43] Similar to Caucasian studies, MetS or its individual components were more frequently diagnosed in PCOS than in controls.…”
Section: Metabolic Syndromementioning
confidence: 73%
“…64 Two studies reported lowest values of systolic (SBP) and diastolic blood pressure (DBP) in patients with normoandrogenic phenotype and healthy controls in comparison to other phenotypes. 24,29 None of East Asian, 14,30-32,44,46,55 Turkish 36,68 or Latin American 37,38 studies demonstrated differences in SBP and DBP or the prevalence of hypertension between the PCOS phenotypes. However, it has been observed that healthy women presented lower values of SBP or DBP in comparison to either all PCOS phenotypes or only to a specific phenotype, most commonly I or II.…”
Section: Caucasian Patients Daskalopoulos Et Al Demonstrated Comparablementioning
confidence: 99%
See 1 more Smart Citation
“…failed to demonstrate a significant difference between PCOS and control groups regarding conventional and Pulsed tissue Doppler parameters of echocardiography 40,41 . A study conducted on PCOS patients in their twenties showed that higher LV mass index and decreased E/A ratio were observed in PCOS patients, which might be suggestive of diastolic dysfunction in its early stage 42 . PCOS women had higher LA diameter, LVMI, and lower LVEF, E/A ratio compared to controls, according to Orio et al 24 .…”
Section: Discussionmentioning
confidence: 99%
“…40,41 A study conducted on PCOS patients in their twenties showed that higher LV mass index and decreased E/A ratio were observed in PCOS patients, which might be suggestive of diastolic dysfunction in its early stage. 42 PCOS women had higher LA diameter, LVMI, and lower LVEF, E/A ratio compared to controls, according to Orio et al 24 And finally, lower peak systolic and diastolic strain rate and peak early diastolic velocity were observed in PCOS patients, suggesting subclinical dysfunction of LV systolic and diastolic activity. 43 PCOS patients are assumed to be at increased risk for CVD 44 and the subclinical LVD is considered as an independent predictor of adverse events in CVD.…”
Section: F I G U R Ementioning
confidence: 91%